2019
DOI: 10.5271/sjweh.3853
|View full text |Cite
|
Sign up to set email alerts
|

Status incongruence in human service occupations and implications for mild-to-severe depressive symptoms and register-based sickness absence: A prospective cohort study

Abstract: The study contributes with a completely novel hypothesis, namely that negative status incongruence between educational attainment and subjective social status may partly explain the excess risk of mental ill-health and sickness absence among employees in human service occupations. The results support this hypothesis with possible implications for associations between established work stressors and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The fact that overqualified individuals in this study had a similar risk of hospitalization for psychiatric disease as job-matched with no academic education, which was not the case for the other disease groups, lends support to a psychological pathway. This is in line with other studies showing an association between overqualification and poor mental health measured through screening instruments validated for detecting risk of psychiatric disorders ( 11 , 31 , 32 ). Regarding the somatic diseases, our results showed that the risk of hospitalization was higher among overqualified workers than among job-matched with an academic education, but lower than among job-matched with no academic education, which may be due to a combination of the above-mentioned factors.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that overqualified individuals in this study had a similar risk of hospitalization for psychiatric disease as job-matched with no academic education, which was not the case for the other disease groups, lends support to a psychological pathway. This is in line with other studies showing an association between overqualification and poor mental health measured through screening instruments validated for detecting risk of psychiatric disorders ( 11 , 31 , 32 ). Regarding the somatic diseases, our results showed that the risk of hospitalization was higher among overqualified workers than among job-matched with an academic education, but lower than among job-matched with no academic education, which may be due to a combination of the above-mentioned factors.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the body of knowledge created around the influence of the level of education on the salaries -as well as on other issues such as job satisfaction or health (Dunlavy et al, 2016;Nyberg et al, 2020;Voces & Cainzos, 2020) -the following main results are shown. Thus, following the statements of the Human Capital Theory, it has been demonstrated that more years of study, in addition to experience and tenure, lead to higher salaries (Liu & Zhang, 2008;García-Pozo et al, 2014;Ons-Cappa et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…For job resources, after expending the effort, the working population usually expects to be rewarded with financial benefits, job security, workplace respect, or expectations of promotions [ 20 , 21 ]. When lacking rewards, employees experience reduced job satisfaction and engagement and may become exhausted, ultimately leading to TI [ 10 , 13 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, people in China attach great importance to their self-image constructed by the evaluations of others [ 23 ]. Individuals always compare themselves to their peers [ 20 ]. Compared to clinicians, the CDC workforce perceives less respect from the community [ 2 ].…”
Section: Introductionmentioning
confidence: 99%